RELIGIOUS MODERATION EDUCATION IN THE FAMILY: A CASE STUDY OF THE BEKASI CITY RELIGIOUS HARMONY FORUM (FKUB) - Asiah, Siti; Rizki Gunawan Hsb, Akmal; Haryono, Pauzan; Putra, Purnama; Gunawan, Syahrul (Edukasi Islami: Jurnal Pendidikan Islam, 2025)
Background: Religious moderation education in the family plays a crucial role in fostering tolerance and peaceful coexistence in a pluralistic society. Purpose: This study explores the implementation of religious moderation education within families through a case study of the Bekasi City Religious Harmony Forum (FKUB). Method: Using a qualitative approach, the research involved in-depth interviews with representatives from Islam, Christianity, Hinduism, Buddhism, and Confucianism, along with document analysis and direct observation of FKUB activities. Result: The findings reveal that each religion emphasizes values such as mutual respect, compassion, and peaceful coexistence. Islam promotes tolerance and dialogue, Christianity focuses on love, Hinduism stresses harmony, Buddhism advocates for virtue and inner peace, and Confucianism teaches respect and harmony. Conclusion: The study concludes that religious moderation education in families contributes significantly to fostering harmony and unity amidst religious diversity in Bekasi City. These findings highlight the potential of early family-based education in building an inclusive and peaceful society.